SOSIALISASI DAN PEMANFAATAN TANAMAN REFUGIA SEBAGAI ALTERNATIF PENGENDALI HAMA TANAMAN - Ilhamiyah Ilhamiyah; Gusti Khairun Ni’mah; Ana Zuraida; Neni Widaningsih (Universitas Islam kalimantan MAB, 2020)
The problem faced by farmers who are members of Gapoktan in the Karang Bunga Village, Mandastana District, Barito Kuala Regency in rice cultivation is pest attack. Farmers always control pest attacks using synthetic pesticides. This causes rice production to be unsafe for consumption because it contains pesticide residues, and can cause the death of natural enemies, resurgence and resistance to pesticides. Therefore it is necessary to conduct socialization and utilization of refugia plants for the conservation of natural enemies and pest control by paying attention to ecological, economic and cultural aspects to create a sustainable agricultural system by suppressing environmental pollution by synthetic pesticides. The method used is to conduct socialization and utilization of refugia plants as agents for controlling pests of rice that are environmentally friendly in the form of socialization through counseling, discussion and demonstration on rice farmers' land. The results of PPM activities are an increase in PPM participant knowledge in terms of knowledge about the use of refugia plant technology; PPM participants gain skills in utilizing refugia plant technology; some PPM participants have started utilizing refugia plant technology by planting rice fields with paper flowers (Zinnia elegans Jaqc)